Do Tax Planning, CSR, and Liquidity Signal Firm Value? Evidence From Indonesian Telecommunication Firms - Qimyatussa'adah Qimyatussa'adah; Mala Sharma; Permatasari Cahyaningdyah; Nika Esti Rahayu; Attaya Ramadhani (Accounting Study Programme Faculty of Economics and Business Universitas Negeri Surabaya, 2026)
Introduction/Main Objectives: This study examines the effects of tax planning, Corporate Social Responsibility (CSR), and liquidity on firm value in telecommunication companies listed on the Indonesia Stock Exchange during the 2020–2024 period. Grounded in signaling theory, this research analyzes how financial and non-financial corporate actions function as signals that influence market valuation. Extending prior research, this study employs three alternative liquidity proxies—Current Ratio, Quick Ratio, and Cash Ratio—to provide a multidimensional perspective on liquidity’s role in shaping firm value Background Problems: do tax planning, csr, and liquidity signal firm value? Novelty: This study introduces a multidimensional liquidity approach and refines signaling theory by demonstrating that financial and non-financial corporate signals are context-dependent, particularly in capital-intensive industries, using evidence from Indonesian telecommunication firms. Research Methods: multiple linear regression analysis on 100 firm-year observations Finding/Results tax planning does not have a statistically significant effect on firm value across all models. Liquidity consistently demonstrates a negative effect, indicating that excessive liquidity may be interpreted by investors as inefficient capital allocation in a capital-intensive industry. CSR shows negative effect only in the Cash Ratio model, suggesting that CSR expenditures may be perceived as reducing financial flexibility when firms maintain high cash holdings. Conclusion: : the study refines signaling theory by demonstrating that corporate signals are context-dependent and that liquidity does not universally function as a positive market signal.